Islamic Microfinance Institutions in Indonesia and The Challenges in the Supply Chain Perspectives - Masyita, Dian (International Journal of Supply Chain Management, 2017)
The Indonesian economy has recently been discouraging. There are more than forty millions Indonesian people living under the poverty line. With supply chains extending throughout microfinance institution, it can be expected to be one of the solution. Though microfinance institutions (MFIs) have different organizational formats, they have to deal with daily management issues. In order to understand the operational structure of different MFIs, this paper assesses their performance by using the Balanced Scorecard (BSC) from four different perspectives. The BSC provides the “balanced” and “integrative” financial and non-financial perspectives of a MFI such as internal business processes, growth and learning, financial and customer perspectives that are extremely important to create a sustainable MFI. This paper reports the results from in-depth interviews with 18 MFI managers in Bandung, Indonesia. The Key Performance Indicators (KPI) of a MFI from four perspectives is identified and the relationships between the different components of BSC are also learned. Overall scores of the BSC reveals BRI to be the best MFI, BPRS as the second, followed by BPR and BMT in the third and fourth place respectively. The advantage of BRI is partly due to robust government support that makes it difficult for other smaller MFIs to compete. In contrast, BMT showed a weak institutional structure in terms of BSC’s elements. It seems that BMT is not well managed according to BSC’s key performance indicators. The results indicate that clients, mostly Muslim, had chose the MFI based on the best performance in daily operations and also those affordable instead of choosing a religious/Shari’ah compliant one.